Pojęcie linii redakcyjnej oraz poszukiwanie jej obrazu w polskiej opinii publicznej i czasopiśmie branżowym w 2017 roku - Furman, Wojciech (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The press law requires the journalist to follow the editorial line. However, attempts to find a clearly formulated editorial line, sought after on the websites of press titles, did not provide unequivocal results. Public opinion polls were only indirectly related to the editorial line. Therefore, the statements of journalists remained to be examined. They have been referred to four normative journalistic social roles. Most often, the role of the reporter and advocate was mentioned, and the role of a debater or moderator of the discussion was the least frequently stated.
The concept of an Editorial Line and the search for its image in Polish Public Opinion and a Trade Magazine in 2017
Keywords: Editorial line; journalistic social roles; public opinion; branch magazine